Revisiting a Nahḍa origin story: Majmaʿ al-Tahdhīb and the Protestant community in 1840s Beirut. (October 2019) - Edwards, Anthony
Abstract: This article is a comprehensive evaluation of the first learned society of the Nahḍa (Renaissance) in Beirut. I argue that Majmaʿ al-Tahdhīb (the Refinement Council, est. 1846) was not a learned society but an ad hoc seminary formed to train converts for itinerant preaching and to build camaraderie among the nascent Protestant confession. In order to unearth the mission of Majmaʿ al-Tahdhīb and amplify the voices of its members – twelve Syrians and two Americans – this essay reconstructs their biographies and the condition of the Protestant community until 1846. This case study explicates the personal and professional entanglements of these fourteen men in terms of social connections, educational opportunities, economic needs, and religious convictions. It contextualizes the early years of several prominent Nahḍa figures by highlighting the material and spiritual aspects of their lives in 1840s Beirut.